Cancer chemopreventive effect of Spirogyra neglecta (Hassall) Kützing on diethylnitrosamine-induced hepatocarcinogenesis in rats - Thumvijit T. (Asian Pacific Organization for Cancer Prevention, 2014)
Spirogyra neglecta, a freshwater green alga, is a local food in the northern and northeastern parts of Thailand. This investigation explored the anticarcinogenicity of S neglecta and its possible cancer chemopreventive mechanisms in rats divided into 14 groups. Groups 1 and 10 served as positive and negative control groups, respectively. Groups 1-9 were intraperitoneally injected with diethylnitrosamine (DEN) once a week for 3 weeks. Groups 10-14 received normal saline instead. One week after the last DEN injection, groups 2-5 were administered for 9 consecutive weeks various doses of S neglecta extract (SNE) and dried S neglecta (SND), mixed with basal diet. Groups 6-9 and 11-14 similarly were administered various doses of SNE and SND starting from the first week of the experiment. Administration of SNE and SND was not associated with formation of glutathione-S-transferase placental form (GST-P) positive foci in rat liver. SNE and SND during initiation phase significantly reduced the number of GST-P positive foci in rats injected with DEN. The number of GST-P also diminished in groups treated with SNE and SND after injection with DEN, except for the low dose extract group. SNE showed stronger anticarcinogenic potency than SND. Furthermore, SNE also decreased the number of Ki-67 positive cells. However, the numbers of TUNEL-positive cells in the liver of the SNE-treated groups were not statistically different from the controls. The GST activity in 50 mg/kg bw of SNE and 1% of SND groups was significantly increased as compared to the positive control. In conclusion, Spirogyra neglecta (Hassall) Kützing showed cancer chemopreventive properties at the early stages of diethylnitrosamine-induced hepatocarcinogenesis in rats. Possible inhibitory mechanisms include enhancement of the activities of some detoxifying enzymes and/or suppression of precancerous cells.